Loss of Insecticides in Managed Amenity Turf: Impacts and Implications. (1st April 2019) - Mann, Ruth
Managed amenity turf in the UK is defined as 'areas of frequently mown, (i.e. mown at least once a week) intensively managed turf, including fields being used for turf production and may include areas for public use including all types of sports turf, golf greens, tees and fairways'. Within managed amenity turf, the most common insect pests are leatherjackets and chafer grubs. These same insects may also be found infesting amenity grassland areas, such as airfields. Damage from these pests includes feeding on grass plants, but also secondary damage caused by birds and mammals searching for the larvae as food. This secondary damage includes ripping out grass tufts and rolling back sections of poorly rooted turf and is often more detrimental than the damage caused by the insects. Until recent years, effective insecticides were available for control of these larvae and reduced impacts, especially on sports turf. However, the UK authorisation for both chlorpyrifos and imidacloprid has been withdrawn. Therefore, no chemical insecticidal control is currently available to turfgrass managers. This article details the effects of leatherjackets and chafer grubs in sportsturf and reviews past and present control measures. Insect pest control in the UK sports turf market has become more difficult due to the withdrawal of two effective insecticides: chlorpyrifos and imidacloprid. Cultural controls may reduce populations, but must be used judiciously to ensure they are not detrimental to the turfgrass themselves. Biological controls can also be effective, but further research is required to ensure optimal use, making them as economically effective as possible. An emergency authorisation of chlorantraniliprole provided effective control of chafer grubs on golf courses and horse race courses in 2018 and it is hoped this product may be fully authorised for use in the future.